1992
DOI: 10.1007/bf00195662
|View full text |Cite
|
Sign up to set email alerts
|

Coaction of light, nitrate and a plastidic factor in controlling nitrite-reductase gene expression in tobacco

Abstract: Nitrite reductase (NIR; EC 1.7.7.1) - a key enzyme of nitrate reduction - is known to be induced by nitrate and light. In the present study with tobacco (Nicotiana tabacum L.) seedlings the dependency of NIR gene expression on nitrate, light and a plastidic factor was investigated to establish the nature of the coaction between these controlling factors. A cDNA clone coding for tobacco plastidic NIR was available as a probe. The major results were as follows: (i) The light effect on the appearance of NIR occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 14 publications
3
20
2
Order By: Relevance
“…It is therefore concluded that the introduced Arabidopsis NiR cDNA was successfully expressed in the transgenic R. umbellata. NiR proteins of A. thaliana (Tanaka et al 1994), spinach (Back et al 1988), tobacco (Neininger et al 1994a), tomato (Migge et al 1998), birch (Friemann et al 1992), and Scots pine (Neininger et al 1994b) reportedly have a molecular mass of 63 kD. These are in line with the western blot (2513,2521,361,362,4331,434,437).…”
Section: Western Blotsupporting
confidence: 61%
“…It is therefore concluded that the introduced Arabidopsis NiR cDNA was successfully expressed in the transgenic R. umbellata. NiR proteins of A. thaliana (Tanaka et al 1994), spinach (Back et al 1988), tobacco (Neininger et al 1994a), tomato (Migge et al 1998), birch (Friemann et al 1992), and Scots pine (Neininger et al 1994b) reportedly have a molecular mass of 63 kD. These are in line with the western blot (2513,2521,361,362,4331,434,437).…”
Section: Western Blotsupporting
confidence: 61%
“…In previous studies on NIR gene expression (Schuster et al 1990b;Seith et al 1991 ;Neininger et al 1992) no quantitative relationship between the transcript level and the rate of enzyme synthesis was observed. It was concluded that regulation at the transcript level is only coarse and does not determine quantitatively the output at the level of the protein which itself is light-or nitratecontrolled.…”
Section: Discussionmentioning
confidence: 63%
“…However, different plant species differ conspicuously in the way nitrate and light regulate NIR gene expression. Regarding control of NIR gene expression in wild-type plants, the differences between mustard, spinach and tobacco reported so far (Schuster and Mohr 1990;Seith et al 1991 ;Neininger et al 1992) can be summarized as follows: (i) In mustard we observed a strong synergism between nitrate and light in enzyme synthesis while the transcript level was unaffected by nitrate but was determined by phytochrome. (ii) In spinach we observed a considerable effect of light on the enzyme level even in the absence of nitrate while the transcript level was unaffected by light and determined by nitrate.…”
Section: Discussionmentioning
confidence: 80%
“…Both red and blue light enhanced NII expression in etiolated tobacco cotyledons, and light effects were only seen when nitrate was present in the growth medium. Light intensity was also important, and increasing light intensity had a positive effect on expression (Neininger et al 1992). Four NII genes are present per haploid Nicotiana genome.…”
Section: Nir and Light Effects In Various Plantsmentioning
confidence: 99%